Urgensi Pendidikan Hukum Digital bagi Generasi Muda dalam Mewujudkan Keadaulatan Siber Nasional - Nur Aripkah; Khairunnisa Noor Asufie (Prosiding Seminar Nasional Ilmu Pendidikan, 2025)
Technological advances have an impact on social change, a shift that was originally done conventionally in the real world but can now be done digitally in cyberspace. The use of the internet is supported by gadgets and applications that make it easier for people in their daily activities to make the statement "world without borders" on digital media true, which will certainly have a positive impact and a negative impact. The young generation based on Law Number 40 of 2009 concerning Youth which is included in the criteria as the young generation refers to those who have an age range of 16 to 30 years old who are the most users in the cyber world. The younger generation as the next generation should get efforts to prevent negative impacts. The provision of education about digital literacy and its wise use must be carried out by education providers by including material in subjects or courses so that all young generations are able to acquire this knowledge. Cyber sovereignty is a concept that refers to the contribution of state control over the internet domain within its borders, including political, economic, cultural, and technological activities. The young generation who have received education is expected to be able to carry out national cyber sovereignty well. This study uses an empirical juridical research method. The purpose of this study is to provide input related to the urgency of digital legal education and an overview of the digital education model.